Hydrochloric acid producing higher purity of glucosamine than sulfuric acid: a comparison study with different detection approaches - Yosita Kornrawudaphikasama; Natwikar Laokua; Nutnicha Rittiyan; Rachaneekorn Klinsalee; Yothawut Tonawut; Nathanan Preechaphonkul; Narongwit Pikulthong; Cherdsak Maneeruttanarungroj (Polish Journal of Chemical Technology, 2024)
Abstract In this study, HCl and H 2 SO 4 were used to compare the best conditions for producing glucosamine from the dry chitin of shrimp shells. The results showed that for HCl hydrolysis, the most favored conditions were 12 M, 80 °C, 2 hours, and a chitin-to-acid volume ratio of 1:20, whereas, for H 2 SO 4 hydrolysis, the most favored conditions were 6 M, 90 °C, 5 hours, and a chitin to acid volume ratio of 1:20. HCl produced pured glucosamine with a higher yield than H 2 SO 4 . Additionally, our findings indicated that glucosamine could be detected using a UV detector with a weak signal, whereas we recommended using an RI detector for a comparably stronger signal. Our production maximum yield of 283.9 ± 13.8 mg Gln g −1 chitin from HCl hydrolysis was comparable to that of other studies, with a comparison between using HCl and H 2 SO 4 being highlighted.
Keywords: Carbohydrate Chemistry and Synthesis; Chemical Synthesis and Reactions; Glycosylation and Glycoproteins Research